Pharmacodynamics‐based approach for efficacious human dose projection of BMS‐986260, a small molecule transforming growth factor beta receptor 1 inhibitor. (8th January 2021) - Parrish, Karen E.; Swanson, Jesse; Cheng, Lihong; Luk, Emily; Stetsko, Paul; Smalley, James; Shu, Yue‐Zhong; Huang, Jinwen; Pabalan, Jonathan G.; Sun, Yongnian; Zvyaga, Tatyana; Cvijic, Mary Ellen; et al.
Abstract: Transforming growth factor beta (TGF‐β) is a pleiotropic cytokine that has a wide array of biological effects. For decades, tumor biology implicated TGF‐β as an attractive therapeutic target due to its immunosuppressive effects. Toward this end, multiple pharmaceutical companies developed a number of drug modalities that specifically target the TGF‐β pathway. BMS‐986260 is a small molecule, selective TGF‐βR1 kinase inhibitor that was under preclinical development for oncology. In vivo studies across mouse, rat, dog, and monkey and cryopreserved hepatocytes predicted human pharmacokinetics (PK) and distribution of BMS‐986260. Efficacy studies of BMS‐986260 were undertaken in the MC38 murine colon cancer model, and target engagement, as measured by phosphorylation of SMAD2/3, was assessed in whole blood to predict the clinical efficacious dose. The human clearance is predicted to be low, 4.25  ml/min/kg. BMS‐986260 provided a durable and robust antitumor response at 3.75  mg/kg daily and 1.88  mg/kg twice‐daily dosing regimens. Phosphorylation of SMAD2/3 was 3.5‐fold less potent in human monocytes than other preclinical species. Taken together, the projected clinical efficacious dose was 600 mg QD or 210 mg BID for 3 days followed by a 4‐day drug holiday. Mechanism‐based cardiovascular findings in the rat ultimately led to the termination of BMS‐986260. This study describes the preclinical PK characterization and pharmacodynamics‐based efficacious dose projection of a novel small molecule TGF‐βR1 inhibitor. Abstract :